A 1, 200-year-old ground-stone object from South Western Torres Strait (northeast Australia) and its implications for historicising ethnographically known social networks. Issue 2 (3rd May 2020) - Ash, Jeremy; Mialanes, Jerome; Brady, Liam M.; von Gnielinski, Friedrich E.; ,
Abstract: Ground-stone objects such as stone-headed clubs ( gabagab ) and axes/adzes held key positions in ethnographically known social networks encompassing Torres Strait and southern central New Guinea. However, the antiquity of ground-stone artefacts in this region is poorly understood given the small number of ground-stone objects found in dated archaeological contexts. We report on the discovery of a 1, 200-year-old fragment of a ground-stone implement recovered from an archaeological excavation at a Kaurareg campsite on the south coast of Muralag in southwest Torres Strait. We discuss this find relative to the dataset of dated ground-stone objects available for the region and consider implications for understanding socio-demography, identity markers, and the development of social networks in Torres Strait. Abbreviations: var.: variation; PNG: Papua New Guinea